1) у=√(-7/(х²+3х) - (х-1)/(х+1)
{ -7/(x²+3x) >0 {-7/(x(x+3)) >0
{x+1≠0 {x≠-1
-7/(x(x+3)) >0
7/(x(x+3) <0<br>7x(x+3) <0<br>x=0 x=-3
+ - +
------ -3----- 0 -------
x∈(-3; -1) ∨ (-1; 0) - область определения функции
2) у=(√(х²-4х))/5 - 3/(х+2)
{x²-4x≥0 {x(x-4)≥0
{x+2≠0 {x≠-2
x(x-4)≥0
x=0 x=4
+ - +
---- -2 --0--------4--------
x∈(-∞; -2)∨(-2; 0] ∨ [4; ∞) - область определения функции
3) у=√9-х² - (5х-2)/√х²+3х-4
{9-х²≥0
{х²+3х-4>0
x²+3x-4=0
D=9+16=25
x=(-3-5)/2=-4
x=2/2=1
x²+3x-4=(x+4)(x-1)
{(3-x)(3+x)≥0
{(x+4)(x-1)>0
(3-x)(3+x)≥0 (x+4)(x-1)>0
x=3 x=-3 x=-4 x=1
- + - + - +
----- -3 ----- 3 ------ ------ -4 ------- 1 -------
+ - +
--- -4 --- 1 ---------
x∈(1; 3] - область определения функции